A framework for scabies control. - Daniel Engelman; Michael Marks; Andrew C Steer; Abate Beshah; Gautam Biswas; Olivier Chosidow; Luc E Coffeng; Belen Lardizabal Dofitas; Wendemagegn Enbiale; Mosoka Fallah; Elkhan Gasimov; Adrian Hopkins; et al. (Public Library of Science (PLoS), 2021)
Scabies is a neglected tropical disease (NTD) that causes a significant health burden, particularly in disadvantaged communities and where there is overcrowding. There is emerging evidence that ivermectin-based mass drug administration (MDA) can reduce the prevalence of scabies in some settings, but evidence remains limited, and there are no formal guidelines to inform control efforts. An informal World Health Organization (WHO) consultation was organized to find agreement on strategies for global control. The consultation resulted in a framework for scabies control and recommendations for mapping of disease burden, delivery of interventions, and establishing monitoring and evaluation. Key operational research priorities were identified. This framework will allow countries to set control targets for scabies as part of national NTD strategic plans and develop control strategies using MDA for high-prevalence regions and outbreak situations. As further evidence and experience are collected and strategies are refined over time, formal guidelines can be developed. The control of scabies and the reduction of the health burden of scabies and associated conditions will be vital to achieving the targets set in WHO Roadmap for NTDs for 2021 to 2030 and the Sustainable Development Goals.